(untitled) (Journal of the College of Basic Education, 2023)
A Bedouin tribe, large in number, strong-willed, and difficult to practice.Saba bin Arfaa bin Malik bin Jashim bin Khaiwan bin Nof bin Hamdan, and Hamdan is the belly ofQahtan (1). They were called the Ajmans, referring to one of their ancestors who had an agama (speech) in his tongue.Not as some claim that they are Ajam (2).The original home of this tribe is the Najjarn region, from which it migrated to the east, and inhabited the province ofAl-Ahsa to the south of the home of the Bani Khalid tribe during the rule of Saudi Prince TurkiIbn Abdullah (1824-1834).The political and military activity of the Ajman tribe:The Ajman tribe appeared on the scene of political events in Najd during the days of Turkish rule.Ibn Abdullah, when her sheikhs tried to get close to the Saudi prince, hoping to obtain aHis confidence in giving them a better place than their original home (the carpenters), and this plan of theirs was well received.A quick response by Prince Turki bin Abdullah, who was aspiring to eliminate the influence ofThe Bani Khalid tribe, which was known for its hostility to the rule of Al Saud. That’s why they were allowed to stay in the homes of BaniKhaled, and provided them with assistance that would enable them to reorganize the tribe in the hope that they would stand up toHis side in the face of the Bani Khalid tribe, to limit its influence (3).The Ajman tribe, under the leadership of its sheikh Falah bin Hathleen, was able to become an influential forceIt is feared by the tribes of the region, a source of confusion for the entity of the Saudi state itself (4). AlthoughThe attention that this tribe received from the Saudi ruler, however, it soon revolted.